Bladder and Bowel Dysfunction Rehabilitation in Children with Acquired Brain Injury - Rita Chiminello; Chiara Pellegrino; Noemi Deanesi; Giulia Barone; Ida Barretta; Gaia Paolella; Maria Luisa Capitanucci; Antonio Maria Zaccara; Maria Laura Sollini; Giacomo Esposito; Donatella Lettori; Gessica Della Bella; et al. (MDPI AG, 2024)
Objective: To evaluate neurogenic bladder and bowel dysfunction (NBBD) in children with cerebral palsy (CP) and acquired brain injury (ABI), a condition considered less frequent in those patients than in children with spinal cord injury (SCI), and to study the relationship between NBBD and disability grade in this population. Study Design: We retrospectively reviewed the clinical data of all patients (aged 3-18 years old) admitted during a three-month observation in our neurorehabilitation department. Data collected were as follows: demographic parameters; disability status (Wee-FIM Scale, Gross Motor Function Classification System (GMFCS) and the Communication Function Classification System); and gastrointestinal and urological symptoms (diaries, Bristol scale, Pad Test and International Consultation on Incontinence Modular Questionnaire). Results: Sixty patients were enrolled (31 females, 29 males): 30 CP, 17 ABI, 3 SCI, and 10 others with neurological diseases. All presented urinary incontinence without gender differences. CP and ABI had major incidences of bowel dysfunction (50% and 64.7%, respectively) and SCI of urinary tract infections (66.6%) and enuresis (100%). A major incidence of symptoms was recorded in patients with higher GMFCS levels (level 3-4-5). Conclusions: NBBD has a high frequency in children with CP and ABI, as in SCI. More attention is needed from pediatricians and pediatric urologists for this clinical entity. Further studies are needed to better understand clinical relevance and, therefore, to establish specific management.